2003
DOI: 10.1210/jc.2003-030617
|View full text |Cite
|
Sign up to set email alerts
|

Early Endocrine, Metabolic, and Sonographic Characteristics of Polycystic Ovary Syndrome (PCOS): Comparison between Nonobese and Obese Adolescents

Abstract: Approximately half of all women with polycystic ovary syndrome (PCOS) are overweight or obese, and studies have reported endocrine and metabolic differences between lean and obese women with PCOS. PCOS has not been as extensively investigated in the adolescent population. The objectives of our study were to further characterize early endocrine and metabolic alterations in adolescents with PCOS and to determine whether differences between nonobese and obese women with PCOS are present early in its course. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
4
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(187 citation statements)
references
References 69 publications
14
157
4
10
Order By: Relevance
“…In a study of 22 obese adolescents with PCOS, only one participant (4.5%) had IGT (Bridger et al 2006), whereas other studies of obese adolescents with PCOS have reported IGT rates as high as 33-52% , Palmert et al 2002. By contrast, nonobese adolescents with PCOS have not been reported to have an increased risk of IGT (Silfen et al 2003), suggesting the underlying relationship between IGT and obesity.…”
Section: Discussionmentioning
confidence: 92%
“…In a study of 22 obese adolescents with PCOS, only one participant (4.5%) had IGT (Bridger et al 2006), whereas other studies of obese adolescents with PCOS have reported IGT rates as high as 33-52% , Palmert et al 2002. By contrast, nonobese adolescents with PCOS have not been reported to have an increased risk of IGT (Silfen et al 2003), suggesting the underlying relationship between IGT and obesity.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, nine studies conducted between 2003 and 2013 were identified, and seven were used in this review (8)(9)(10)(11)(12)(13)(14). Two studies were excluded from our analysis because there was a lack of ultrasonographic quantitative data (15,16).…”
Section: Results Of Ovarian Ultrasound Studies In Adolescentsmentioning
confidence: 99%
“…The overall mean ovarian volume was 9.29 ± 4.62 cm 3 for PCOS patients and 4.77 ± 2.30 cm 3 for controls (p < 0.001). This was calculated using studies that had both PCOS and control patients (9,11,13). The morphology of ovarian follicles was reported in three of the studies, which showed peripheral and multiple follicles ( > 10) in 83% of cases (10,11,14).…”
Section: Ultrasound (2d) and Biochemical Features Of Studies Includinmentioning
confidence: 99%
“…[23] Yap›lan testlerle hiperandrojenemi tan›s› için total testosteron 55 ng/dl, serbest testosteron 6.3 pg/ml, androstenodion 2.45 ng/ml ve/veya DHEA-S 2480 ng/ml üzerinde olmas› gerekir. [24] Fruzzetti F. ve arkadafllar› ise total testosteron 80 ng/dl üzerinde ve/veya serbest testosteron 3.6 pg/ml üzerinde ve/veya DHEAS 3600 ng/ml üzerinde …”
Section: De¤erlendirmeunclassified